Protecting mental health in quarantine: Exploring lived experiences of healthcare in mandatory COVID-19 quarantine, New South Wales, Australia - Penelope Fotheringham; Edwina Dorney; Shannon McKinn; Greg J. Fox; Sarah Bernays (Elsevier, 2023)
Objectives: In response to the COVID-19 pandemic, Australia implemented mandatory hotel quarantine for returned international travellers from March 2020-November 2021. Healthcare was rapidly transformed and scaled up to facilitate delivery of face-to-face and virtual healthcare within quarantine facilities. We sought to understand, from the patient perspective, what a virtual model of healthcare may need to be aware of to respond to, protect, and mitigate people's mental health within a 'public health protection' context of quarantine. Design: Qualitative study design using in-depth semi-structured interviews exploring experiences of the virtual model of healthcare in quarantine. Setting: Special Health Accommodation (SHA) quarantine facilities following Australian Federal and New South Wales (NSW) State quarantine policy, NSW, Australia. Participants: 25 returned international travellers aged 18 years or older of any COVID-19 status who quarantined within SHA between October 2020-March 2021. Results: Participants identified three broad areas of concern. Firstly, their potential to transmit COVID-19, that created anxiety for all participants. Secondly, the effects of losing personal freedoms in quarantine to protect the wider Australian community. Thirdly, many participants entered quarantine during intense biographical moments in their lives, compounding the stress of their experience. Participants felt lost within the 'faceless' quarantine administrative system they navigated prior to their actual arrival in Australia and during their mandated quarantine period. This cumulative experience compromised their expectations and experiences of person-centred care once in quarantine. Conclusions: Quarantine has been a critical public health measure for managing COVID-19 in Australia. The pandemic provides opportunities to learn from quarantine implementation. Participants struggled to separate healthcare provision from the broader quarantine systems and processes. Due to this confusion, blame was directed at healthcare providers for many, and in some cases all difficulties, including those encountered getting into and once within quarantine. Valuable lessons can be learnt from engaging with patients' perspectives to adapt and strengthen future quarantine to deliver responsive, person-centred healthcare.